The effect of stimuli with and without time-out on stuttering - S, Basavaraj (Journal of All India Institute of Speech and Hearing)
There are several studies indicating that stuttering decreases when time-out is made contingent with stuttering. Most of these studies have used visual or auditory stimuli to indicate the occurrence of stuttering and to be silent for the required duration as time-out. Thus, there are two factors in the process of time-out. It was the purpose of the present study to find out the effect of visual or auditory stimuli with time-out from speaking or reading and the effect of visual or auditory stimuli only.